2021
DOI: 10.1177/17562848211032126
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic and atherosclerotic cardiovascular events in inflammatory bowel disease: epidemiology, pathogenesis and clinical management

Abstract: Inflammatory bowel disease (IBD) is associated with an increased risk of cardiovascular disease (CVD). The increased risk of CVD concerns an increased risk of venous thromboembolism (VTE), atherosclerotic cardiovascular disease (ASCVD) and heart failure (HF), at corresponding relative risks of 2.5, 1.2 and 2.0, respectively, as compared with the general population. Especially young patients under the age of 40 years run a relatively high risk of these complications when compared with the general population. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…Chronic systemic inflammation is considered a key factor for endothelial dysfunction and increased arterial stiffness, which was closely associated with atherosclerosis 23 . Patients with chronic inflammatory diseases, such as rheumatoid arthritis, psoriasis, and systemic lupus erythematosus, were reported to have an increased risk of arterial thromboembolic events 24 . IBD is a group of non‐specific inflammatory diseases of the intestine, characterized by chronic relapsing and remission inflammation 1,2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic systemic inflammation is considered a key factor for endothelial dysfunction and increased arterial stiffness, which was closely associated with atherosclerosis 23 . Patients with chronic inflammatory diseases, such as rheumatoid arthritis, psoriasis, and systemic lupus erythematosus, were reported to have an increased risk of arterial thromboembolic events 24 . IBD is a group of non‐specific inflammatory diseases of the intestine, characterized by chronic relapsing and remission inflammation 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Patients with chronic inflammatory diseases, such as rheumatoid arthritis, psoriasis, and systemic lupus erythematosus, were reported to have an increased risk of arterial thromboembolic events. 24 IBD is a group of non-specific inflammatory diseases of the intestine, characterized by chronic relapsing and remission inflammation. 1,2 A meta-analysis of 41 studies showed that patients with IBD exhibit significant endothelial dysfunction, increased arterial stiffness, and carotid intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the coagulation cascade and proinflammatory cytokines as a consequence of active intestinal inflammation may be a factor that contributes to the occurrence of acute arterial events [ 36 ]. Disease activity should be regarded as a modifiable risk factor for cardiovascular events, and aggressive control of inflammation might reduce the risk of thrombosis in patients with IBD.…”
Section: Risk Factors For Ihd In Ibd Patientsmentioning
confidence: 99%
“…Moreover, important clinical risk factors predisposing IBD patients to VTE are not taken into account. Over the past decade, studies identified disease flare, frequent or prolonged hospitalization, surgery, and extensive colonic disease as such [5]. The European Crohn's and Colitis Organisation (ECCO) guideline recommends treating all admitted IBD patients with thromboprophylaxis to reduce VTE risk, irrespective of the indication for hospitalization.…”
mentioning
confidence: 99%
“…An important gap in current knowledge is the additional risk-enhancing effect of IBD diagnosis and accompanying disease characteristics. The literature provides important clues regarding IBD-specific risk factors that might be useful for accurate CVD risk estimation [5]. CVD risk appears to be associated with disease flares (specifically the 3 months before and after hospitalization), disease location (higher risk for colonic involvement as compared to ileal/ileocecal disease in those with Crohn's disease), and the extent of inflammation (higher risk in individuals with pancolonic UC than those with distal colitis/proctitis).…”
mentioning
confidence: 99%